The geochemical and geochronological properties of postcollision a-type magmatism (Keban-Elazığ-Turkey) - Ertürk, Mehmet Ali; Sar, Abdullah; Rizeli, Mustafa Eren (My University, 2020)
In this study, the petrographic, geochemical and geochronological characteristics of Late Cretaceous-Middle Eocene Keban igneous rocks were examined in Keban-Elazığ-Turkey. Igneous rocks in the study area are represented by syenite porphyry and quartz monzonites. Petro-graphically, the main mineral paragenesis of rocks showing holocrystalline texture are K-feldspar (Mega-phenocrystalline) + plagioclase ± amphibole ± biotite ± quartz minerals. Secondary mineral phases are represented by calcite, sericite, chlorite and epidote minerals.Accessory mineral phases consist of sphene, apatite, zircon, garnet, pyrite, fluorite and opaque minerals. According to some analysis results, SiO2 (60.09 – 64.37 wt.%), Al2O3 (15.75 – 17.96 wt.%), Fe2O3 (1.18 – 5.30 wt.%), MgO (0.09 – 0.92 wt.%) CaO (2.07 – 4.27 wt.%), Na2O (0.80 – 4.93 wt.%) , K2O (4.69 – 13.42 wt.%), TiO2 (0.22 – 0.37 wt.%), P2O5 (0.05 – 0.26 wt.%), Na2O + K2O (8.22 – 14.22), Zr (200.9 – 665.4 ppm), Hf (4.6 – 18.4 ppm), Ta (1.5 – 2.7 ppm), Nb (24 – 56 ppm) ranges between values. The chondrite normalized rare earth element (REE) patterns display enrichment of light rare earth elements (LREE) compared to the heavy rare earth elements (HREE). The primitive mantle normalized trace element patterns indicate that the large ion lithophile elements (LILE) enriched compared to the high field strength elements (HFSE). According to LA-ICPMS zircon U-Pb crystallization ages ranges between 46.1 ± 0.5, 76.3 ± 0.3, 76.36 ± 0.34 and 77.4 ± 0.3 My. (Late Cretaceous-Middle Eocene). In the tectonic environment diagrams the studied rocks fall into the post-collisional fields (developing after collision). These rocks fall into the A-type granitoid areas and are of shoshonitic character. It falls into the post-collisional region (developed after collision) in the tectonic environment diagrams of the rocks studied. According to the field, petrography, geochemical and geochronological studies are evaluated together, Keban Magmatic rocks are thought to have the characteristics of post-collision developed magmatism.
Bildiri - Yayımlanmış
Keywords: Post-collision magmatism; Keban; Elazığ; Late cretaceous-middle eocene